MONITORING TOOLS TO ASSESS VEGETATION SUCCESSIONAL REGRESSION AND PREDICT CATASTROPHIC SHIFTS AND DESERTIFICATION IN MEDITERRANEAN RANGELAND ECOSYSTEMS (Desertification in the Mediterranean Region a Security Issue)
The relationship between grazing intensity and ecosystem performance is complex and can depend on the prevailing ecological conditions. Previous studies have revealed that, in traditional grazing ecosystems, grazing can reduce ecosystem diversity in poor soils, but increase diversity and productivity in rich ecosystems subject to moderate grazing pressure. We are interested in detecting long-term structural changes or drift in an ecosystem before it is too late to prevent irreversible degradation. We analyzed vegetation spatial patterns and complexities of four Mediterranean communities: Tihmadit Region (Middle Atlas, Morocco), Camiyayla (Namrum) Region (Taurus Mountain, Turkey), Sykia Region (south of the Sithonia Peninsula, Greece), and Cabo de Gata Nijar Natural Park, Spain. Grazing disturbance was most intense near shelter and water points, which lead to gradients in soil surface disruption, compaction, and changes in the composition and cover of perennial vegetation. Dense matorral was more resistant to species loss than were moderately dense and scattered matorral, and grassland. Information fractal dimension decreased as we moved from a dense matorral to a discontinuous matorral, and increased as we moved to a more scattered matorral and to a grassland, which resulted in two opposing processes (interaction declining with ecosystem development, and immigration increasing with degradation) in a common pattern, i.e., small patches homogeneously distributed in the landscape. Characteristic species of the natural vegetation declined in frequency and organization in response to higher grazing disturbance, while species of disturbed areas exhibited the opposite trend. Overall, the spatial organization of the characteristic plants of each community decreased with increasing vegetation degradation, with the intensity of the trend being related to the species’ sensitivity to grazing. Developmental instability analyses of key species were used to determine the sensitivity of dominant key species to grazing pressure. Palatable species, which are better adapted to being eaten, such as Periploca laevigata, Phillyrea latifolia and Genista pseudopilosa, were able to resist moderate grazing pressure, while species of disturbed, grazed sites did not change developmental instability in response to increasing grazing pressure, such as Thymus hyemalis, Teucrium lusitanicum and Cistus monspeliensis. The usefulness of these monitoring tools in preventing land degradation is discussed.

Dendrochronology of Quercus ilex L. and its potential use for climate reconstruction in the Mediterranean region (Canadian Journal of Forest Research, 2009)
Holm oak (Quercus ilex L.) is a long-lived species widely distributed across the Mediterranean Basin, with potential value for dendrochronology and dendroclimatology. However, tree-ring dating in Q. ilex is a complex task that has limited the number of dendrochronological studies using this evergreen species. In the present work, it was investigated if old Q. ilex trees showed annual tree rings and whether they can be used as climate proxies. A long tree-ring chronology (126 years) of Q. ilex was developed using cross sections of 20 trees from the Guadiana river basin (Portugal). The high correlation among tree-ring series suggested that tree growth was controlled mainly by climate. Response function analysis showed a positive correlation between tree-ring width and precipitation from October(t–1) of the previous year to January(t) of the current year and in May(t). Tree-ring width was negatively correlated with the North Atlantic oscillation that exerts a strong influence on the precipitation over Iberia. Negative pointer years were triggered by dry years and became more frequent during the last decade of the 20th century. In conclusion, it is possible to accurately date old Q. ilex trees, and their tree rings could be used for climate reconstructions across the Mediterranean.
doi: 10.1139/X09-163

Relationships between climate and double rings in Quercus ilex from northeast Spain (Canadian Journal of Forest Research, 2007)
The influence of climatic factors on tree-ring width and the formation of double rings was studied in Quercus ilex L. growing in a coppice stand left unmanaged for 22 years. Ten trees were felled and discs were taken every 30 cm from bole and dominant branches. Dendrometer bands were installed on 10 nearby trees and the data recorded were used to confirm the accuracy of our tree-ring identification. They were also used to relate the seasonal radial growth pattern to double-ring formation. Double rings were frequent and occurred consistently along the stem. Two types of double rings could be recognized according to their width: type I, with the extra growth band accounting for approximately 50% of the tree ring; and type II, with a narrow extra growth band. Type I double rings were formed when approximately 1/2 of the growing-season precipitation occurred during the second growth period of the season and after the summer drought. Type II double rings occurred when approximately 1/3 of the precipitation in the growing season occurred after the summer drought. The formation of double rings was triggered by rainfall in summer and the extra growth-band width was related to summer and autumn environmental conditions. Double rings in Q. ilex can potentially be used in dendroclimatological studies, as they are formed in response to climatic conditions within the growing season.
doi: 10.1139/X07-050

Analysis of serpentinophytes from north-east of Portugal for trace metal accumulation--relevance to the management of mine environment. (Chemosphere, 2004)
In north-east of Portugal, the serpentinized area is about 8000 ha with a characteristic geology and flora. The serpentine plant community and respective soils were analyzed to examine the trace metal budget in different tissues of the plants exhibiting resistance to trace metals. One hundred and thirty five plant species belonging to 39 families and respective soils have been analyzed for total Co, Cr, Cu, Fe, Mn, Ni, Pb and Zn. Substantial amounts of Ni, Cr, Co and Mn were detected in plant tissues which are listed below: NI: Alyssum serpyllifolium (38105); Bromus hordeaceus (1467); Linaria spartea (492); Plantago radicata (140); Lavandula stoechas (118) and Cistus salvifolius (114); CR: L. spartea (706.7); Ulmus procera (173.4); A. serpyllifolium (129.3); Cistus ladanifer (40.8); L. stoechas (29.5); P. radicata (27.81); Setariopsis verticillata (25.7); Plantago lanceolata (24); Digitalis purpurea (23.4); Logfia minima (23.1); Arenaria querioides (23); Hieracium peleteranum (22.7); Arenaria montana (14.5); CO: A. serpyllifolium (145.1); L. spartea (63.2); P. radicata (10.4); H. peleteranum (7.3); Lepidium heterophyllum (6.9); A. querioides (6.6); C. salvifolius (6.5); C. ladanifer (6.3); L. stoechas (6.1); Anthyllis lotoides (6.1); L. minima (6.1); Euphorbia falcata (5.7) and B. hordeaceus (5.6); MN: A. serpyllifolium (830); L. spartea (339); L. stoechas (187.1); L. minima (182.7); Castanea sativa (125); Spergula pentandra (124); P. radicata (119); Cytisus striatus (115.4); Quercus pyrenaica (110); Teucrium scorodonia (109.4); Fraxinus vulgaris (109); Anthyllis sampaiana (108); Quercus ilex (108). The significance of serpentine flora, need for conservation of these fragile and environmentally invaluable plant resources for possible use for in situ remediation of metalliferous substrates are presented in this paper.

Drosophyllum lusitanicum, an endangered West Mediterranean endemic carnivorous plant: threats and its ability to control available resources (BOTANICAL JOURNAL OF THE LINNEAN SOCIETY, 2002)
Drosophyllum lusitanicum (L.) Link (Droseraceae), Erva pinheira orvalhada, an endangered carnivorous plant, is a local endemic of clearings in pine, cork oak and oak forests or their successional shrublands in the western Iberian Peninsula and Morocco. The conservation status, distribution and population dynamics of this species are only partially known, both for Spanish and Portuguese occurrences. Portuguese distribution data from herbarium and bibliographic sources were collected for this study. Field work on 50 populations was undertaken in order to improve knowledge on their conservation status and possible threats. Natural causes, infrastructure and housing construction are stressed as the most important threats. Germination tests were carried out and the distribution patterns, plant height and the number of flowers were studied in an arbitrarily chosen population. A relatively high light requirement and low competitive ability to gain light are considered factors likely for the microdistribution pattern. Drosophyllum lusitanicum cannot compete for light in habitats with intense competition. Seeds from D. lusitanicum have reduced probability of germination when adult plants are already growing in the area. It is hypothesized that seed germination shows a similar pattern to flowering, viz over a considerable time rather than in a sudden flush. This strategy may be a key factor for the species' survival, representing attempts to take advantage of available resources, preventing intraspecific competition and, finally, preventing sudden total disappearance of a population, resulting from any catastrophic events due to natural causes or to human activity. As a result of this study, some conservation measures are suggested. (C) The Linnean Society of London.

Removal of toxic metals from solution by leaf, stem and root phytomass of Quercus ilex L. (holly oak). (Environmental pollution (Barking, Essex : 1987), 2000)
Increased consciousness for safeguarding the aqueous environment has prompted a search for alternative technologies for the removal of toxic metal ions from aqueous solutions. In this regard, a wide variety of biomass is being considered as adsorbents of heavy metals for treatment of industrial and domestic wastewaters as well as natural waters, including drinking water. In the present investigation, the potential of Quercus ilex phytomass from stem, leaf and root as an adsorbent of chromium (Cr), nickel (Ni), copper (Cu), cadmium (Cd) and lead (Pb) at ambient temperature was investigated. The metal uptake capacity of the root for different metals was found to be in the order: Ni>Cd>Pb>Cu>Cr; stem Ni>Pb>Cu>Cd>Cr; and leaf Ni>Cd>Cu>Pb>Cr. The highest amount adsorbed was Ni (root>leaf>stem). Data from this laboratory demonstrated that Ni is sequestered mostly in the roots, where concentrations can be as high as 428.4 ng/g dry wt., when 1-year-old seedlings were treated with Ni (2000 mg/l) in pot culture experiments, compared to 7.63 ng/g dry wt., control (garden and greenhouse soil) topsoil where Ni was present in trace amounts. This proves that the root biomass of Q. ilex has the capacity for complexing Ni. Cr exhibited the least adsorption values for all the three types of phytomass compared to other metals. The trend of adsorption of the phytomass was similar for Ni and Cd, i.e. root>leaf>stem. Desorption with 10 mM Na(4) EDTA was effective (55-90%) and, hence, there exists the possibility of recycling the phytomass. The biosorption results of recycled phytomass suggest that the selected adsorbents are re-usable. The advantages and potential of the Q. ilex phytomass as a biofilter of toxic trace metals, the scope and need for enhancing the efficiency of the Q. ilex phytomass as an adsorbent of metals are presented.

Dendroanalysis: a tool for biomonitoring environmental pollution? (The Science of the total environment, 1999)
Trees of temperate regions usually form visible annual growth rings, which can be dated accurately. It is therefore possible to collect wood samples of different age and analyse their heavy metals content in order to get a chronological record of trace elements pollution in the tree's environment. This method of retrospective biomonitoring was called dendroanalysis. A basic assumption of dendroanalysis is the stability of the mineral distribution patterns, i.e. once the elements are stored, no significant mobility should occur. Additionally, neighbouring trees growing in the same environment should show similar radial element patterns. While some studies presented good correlations between radial distributions of heavy metals in tree rings and temporal records of pollution from industry or traffic, others failed in using dendroanalysis as a chronological record of pollution. Probably some elements can move at a certain rate in radial direction through the ray parenchyma cells. In this way the radial element distributions are subsequently changed. Growth rates of tree rings can also influence the concentrations of elements in wood. During periods of slow growth higher concentrations of elements can be found in the wood. Therefore, radial distribution patterns of heavy metals in tree rings should be used with caution as a tool for retrospective biomonitoring of environmental pollution.

Radial distribution of Ni in stemwood of Quercus ilex L. trees grown on serpentine and sandy loam (umbric leptosol) soils of NE-Portugal (Plant and soil, 1996)
Concentrations of Ni were determined in xylem and phloem of Quercus ilex trees growing on serpentine and sandy loam soils of northeast Portugal. Radial distribution patterns of Ni in stemwood were compared to variations in annual growth increments of the trees. Concentrations of Ni in xylem and phloem were higher in Q. ilex from serpentine soil, when compared with Q. ilex of a sandy loam soil. The radial distributions of Ni showed large variations among the trees, although they all grew in the same area within a short distance from each other. These differences can be caused by small-scale spatial variations in the soil. Therefore, the use of such radial Ni distributions for a retrospective biomonitoring of the Ni pollution of larger areas appears questionable.